(untitled) (Indian Journal of Child Health, 2019)
Background: Visual impairments are associated with cerebral palsy (CP). They enhance functional limitations in children with CP. Objective: The objective of the study was to determine the types of visual impairments in children with CP, and thus the importance of early evaluation and intervention to improve the quality of life. Materials and Methods: Children with CP (n=775) attending the child development clinic from 2012 to 2017 were included in the study. Thorough antenatal, natal, postnatal, and developmental history were recorded. Complete demographic data, anthropometry and general physical, and neurological examination findings were recorded. All patients were advised neuroimaging (computed tomography/magnetic resonance imaging) and hearing and ophthalmological assessment. Results: Of the 775 patients, 270 (34.8%) patients had squint (including convergent and divergent). Detailed fundoscopic and visual evoked potentials (VEP) examination was done in 382 patients. Non-apparent abnormalities (VEP and fundus changes) were seen in 121 patients (31.7%) among 382 tested. Of those 121 patients, VEP changes and fundus changes were seen in 62 and 41 patients, respectively. Refractive errors were detected in 25 patients. Of the total patients assessed for ophthalmological ailments, 129 (33.7%) patients were completely normal. Conclusion: Visual impairments are associated in large percentage of CP patients. Early evaluation and intervention are emphasized to improve the quality of life in these patients.